Praktik Penanganan Gigi Goyang untuk Mahasiswa dan Praktisi Periodonsia: Practical Management of Loose Teeth for Students and Periodontists - Indrawati, Dwi Wahyu; Manurung, Rizky Briliant Syah; Endarti, Esa Wahyu; Mukti, Ria Andriani; Manurung, Muhammad Rizky Akbar (Proceedings of The ICECRS, 2025)
Periodontal disease is a complex oral health condition with a high prevalence and significant impact on quality of life, as well as associations with systemic diseases. Tooth mobility is a critical clinical sign reflecting the severity of periodontal disease and requires appropriate management to prevent tooth loss. A one-day training on the management of mobile teeth was conducted at the Faculty of Dentistry, Universitas Airlangga, aiming to enhance the clinical competence of dental students and practitioners through an evidence-based approach. The training methodology included scientific presentations, clinical case discussions, and pre- and post-training evaluations. Results demonstrated a 28% improvement in participants' knowledge, indicating the effectiveness of the instructional methods. This training contributes substantially to the development of clinical skills, strengthens academic and professional networks, and supports the advancement of periodontal health services in Indonesia. Continuation and expansion of similar programs are recommended as part of ongoing efforts to improve evidence-based dental practice and regenerative technology integration.